The Word I Hate: Racism, Refugees and Asylum Seekers in Iceland - Tryggvadóttir, Helga Katrín; Loftsdóttir, Kristin (Stjórnsýslustofnun, 2020)
Internationally, it has been well documented that refugees and asylum seekers are portrayed as one of Europe’s greatest threats, which intersects strongly with stereotypes about Muslim men. Our discussion focuses on asylum seekers in Iceland in 2015-2017 and their experiences of racism. The analysis shows that asylum seekers experienced racism in Iceland, but that this racism becomes overshadowed by their precarious position as asylum seekers. Our analysis of racism and asylum seekers in Iceland is based on an intersectional perspective that stresses how racism has to be seen as existing in conjunction with other identifications and identities. In our case, the intersection of racism with the position of vulnerability is particularly important, i.e., the vulnerability that these individuals experience when categorized as asylum seekers. As we stress, the asylum seekers’ dismissal of racism signifies the intense insecurity that they live under and the structural violence that they become subjected to from state and border policies.